Answer:
C. Exponential decay
Step-by-step explanation:
Answer:
yea dude thats a whole project you cant just put it on brainly and expect us to do it for you. stop being lazy and abusing the website
Step-by-step explanation:
We can write the equation: x + x + 2 + x + 4 = -48, where x is the least digit and x + 4 is the greatest. We get 3x + 6 = -48, 3x = -54. x = -18, so x + 2 is -20, and x + 4 is -22. Therefore, the 3 consecutive even integers that sum to -48 are -18, -20, and -22.
---
Hope this helps!
Answer:
-6
Step-by-step explanation:
-6/b-50=-49
step1;collect like terms
-6/b=-49+50
-6/b=1
step2;cross multiply
-6/b=1
-6=1b(1b can also be regarded as b)
b=-6